A study of the impact of Malaysian code on corporate governance practices on firm performance in Malaysia - Marlia Shamsudin, Siti; Omar, Norliana; Saatila Mohd Isa, Noor; ., . (International Journal of Engineering and Technology, 2018)
A good corporate governance framework is imperative to improve the corporate governance standards and to establish the roles and responsibilities of the key members of the company. Therefore, considering the importance role of the corporate governance, the aims of this study is to examine the relationship between corporate governance and firm performance by taking into consideration the changes in Malaysia Code on Corporate Governance 2007 (MCCG 2007) and Malaysia Code on Corporate Governance 2012 (MCCG 2012). The sample of this study consists of top 90 firms listed in Bursa Malaysia for the period from 2008 to 2016. The findings indicate that the board independence, board size and board compensation positively and significantly influence the firm performance. On the other hand, CEO duality has a negative impact on firm performance. Thus, the findings of this study shed the light on the significance of practicing good corporate governance to enhance the firm performance.Â Â